IMPLEMENTING NEURO LINGUISTIC PROGRAMMING (NLP) IN CHANGING STUDENTS’ BEHAVIOR: RESEARCH DONE AT ISLAMIC UNIVERSITIES IN ACEH - Salami, Salami (Jurnal Ilmiah Peuradeun, 2015)
The students of Islamic Universities have learned many Islamic books and knowledge. They should behave honestly in the examination because Islam teaches them to be honest. However, it is found that there are students, especially from Islamic Teaching Department, who cheat in the exam. Their knowledge about religion does not affect their attitude and behavior. So, the researcher wants to implement some of NLP techniques and models during the final exam to see if cheating activities done by the students reduced. Before they start doing the exam, the researcher built the rapport with them, and then said something by using certain words that affect their subconscious mind or called hypnotic language patterns. If this massage becomes the program in their mind, it will change their behavior in exam. After implementing some of NLP techniques or models, it shows that the frequency of cheating can be reduced drastically.